Geomorphic knowledge for mangrove restoration: a pan‐tropical categorization. Issue 2 (14th October 2015) - Balke, Thorsten; Friess, Daniel A.
Abstract: Extreme events such as storm surges and tsunamis in combination with subsidence of densely populated coastal areas pose an increasing threat to millions of people in the tropics. Intertidal mangrove forests may form a natural protection against some extreme events, but have also widely been destroyed by coastal development. The establishment of mangroves and the maintenance of their stability over the short‐ to long‐term requires an understanding of sedimentary processes and landforms in the coastal zone, making geomorphology a crucial, but sometimes neglected discipline when attempting restoration for disaster risk reduction. Mangrove geomorphic setting varies markedly across the tropics, depending on abiotic parameters such as suspended sediment supply and tidal range, with different restoration strategies suitable for each. In this study we provide a global categorization of mangrove geomorphic settings, based on the literature and global remote sensing data. The world's mangroves can be broadly defined as: (1) minerogenic and high tidal range; (2) minerogenic and low tidal range; and (3) organogenic and low tidal range. We further discuss restoration and management approaches most suitable for each geomorphic setting. Overall, this study can be used to inform managers about the relevance of geomorphic knowledge for successful mangrove restoration, how an understanding of geomorphology can influence site selection and restoration success, and how to match specific restoration methods to the prevailing geomorphic context. The stronger incorporation of geomorphic knowledge into site planning and design will improve the success rates of restoration for this important and globally threatened ecosystem. Copyright © 2015 John Wiley & Sons, Ltd.